Criticism of the practice of promoting monks to the episcopacy in the letter of Pope Celestine I to the bishops of Southern Gaul - Georgy Zakharov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви, 2024)
The article is devoted to the analysis of the letter of Pope Celestine I to the bishops of Southern Gaul (428). In this text, the Roman pontiff sharply criticizes the church practices that had become widespread in the region, which can be associated with the influence of monasticism on the episcopate: the wearing of the pallium by bishops, the refusal of repentance to dying sinners, the election to episcopal sees of persons who had not consistently passed the stages of the clerical cursus, as well as candidates who had not previously been members of the clergy of the local Church to whose see they were elected and who had not received the support of its clergy and flock. Apparently, Celestine is polemicizing in this case against representatives of the so-called "Lérinian party" – bishops associated with the monastery of Lérins, although similar tendencies, determined by an ascetic rethinking of the episcopal ministry, were associated not only with this monastic center. Without naming the founder of the monastery of Lérins, and at that time already the bishop of Arles, St. Honoratus, Celestine insists on the inviolability of the rights of the metropolitan of Narbonne, thereby denying the inclusion of Narbonensis in jurisdiction of Arles. He also condemns the Gallic bishops for elevating to the episcopacy a certain Daniel, the founder of a monastic community of virgins in the East, who fled to Gaul due to accusations of immoral behavior. As shown in the article, the position of Pope Celestine was determined not only by the political situation and the desire to assert the influence of the Roman See in Gaul, but also by the consistent defense by the Roman See of the model of the local Church, which was based on the principles of strict hierarchy of the clergy and the consent of the bishop and his flock.